Smart Tactics To Improve The Education Quality Through The Management of Education Funds at SD Muhammadiyah Karangharjo - Abdul Hamid Haji Harahap; Sedya Santosa (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2024)
This study aims to directly observe the implementation of education financing management in SD Muhammadiyah Karangharjo. The main focus is to provide an overview of the process of planning education financing (budgeting), implementing education financing (actuating), and monitoring education financing (controlling). The research method used is field research with a qualitative approach—information collected through interviews, observations, documentation, and triangulation. The validity of the data is tested by considering trustworthiness, transferability, dependability, and confirmability. Data analysis includes data collection, reduction, presentation, and verification. The research was conducted at SD Muhammadiyah Karangharjo. It produced findings that education financing planning produces budget efficiency and meets student needs, while the implementation of education financing requires careful organization by utilizing available resources.